2005
DOI: 10.1021/mp0500465
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Thermal and pH Stability of Human Respiratory Syncytial Virus

Abstract: Respiratory syncytial virus (RSV) was studied as a function of pH (3-8) and temperature (10-85 degrees C) by fluorescence, circular dichroism, and high-resolution second-derivative absorbance spectroscopies, as well as dynamic light scattering and optical density as a measurement of viral aggregation. The results indicate that the secondary, tertiary, and quaternary structures of RSV are both pH and temperature labile. Derivative ultraviolet absorbance and fluorescence spectroscopy (intrinsic and extrinsic) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 20 publications
2
58
1
3
Order By: Relevance
“…24 We have also observed that a common mechanism of the destabilization of RSV is pH and temperature induced particle aggregation. 24 In this work, an empirical phase diagram was created employing measurement of the virus by a variety of techniques as a function of pH and temperature. The resultant colored diagram displayed clearly delineated empirical phase boundaries that indicated conditions under which the structure of the virus was altered (i.e., degraded).…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…24 We have also observed that a common mechanism of the destabilization of RSV is pH and temperature induced particle aggregation. 24 In this work, an empirical phase diagram was created employing measurement of the virus by a variety of techniques as a function of pH and temperature. The resultant colored diagram displayed clearly delineated empirical phase boundaries that indicated conditions under which the structure of the virus was altered (i.e., degraded).…”
Section: Introductionmentioning
confidence: 74%
“…RSV samples were further purified by a 30-60% w/v sucrose gradient made in NTE buffer (10 mM Tris-HCl, 140 mM NaCl, 1 mM EDTA) pH 7.4, and concentrated by centrifugation in a 1.45 M sucrose cushion as previously reported. 24,25 Virus titration was performed by an ELISA sandwich using the method of Malley et al as previously reported. 24,26 As determined by ELISA, stock suspensions of purified RSV contained approximately 10 5 to 10 6 PFU/mL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations